Studies of the binding mode of TXNHCH2COOH with calf thymus DNA by spectroscopic methods - Ataci, Nese; Arsu, Nergis (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
In this study, a thioxanthone derivative named 2-(9-oxo-9H-thioxanthen-2ylamino) acetic acid (TXNHCH2COOH) was used to investigate small molecule and DNA binding interactions. Absorption and fluorescence emission spectroscopy were used and melting studies were used to explain the binding mode of TXNHCH2COOH-DNA. Intrinsic binding constant K-b TXNHCH2COOH was found 6 x 10(5) M-1 from UV-Vis absorption spectroscopy. Fluorescence emmision intensity increased by adding ct-DNA to the TXNHCH2COOH and KI quenching experiments resulted with low k(sv) value. Additionally, 3.7 degrees C increase for T-m was observed. The observed quenching of EB and ct-DNA complex and increase viscosity values of ct-DNA by addition of TXNHCH2COOH was determined. All those results indicate that TXNHCH2COOH can intercalate into DNA base pairs. Fluorescence microscopy helped to display imaging of the TXNHCH2COOH-DNA solution. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Intercalation; Thioxanthone derivative; Calf thymus DNA; Spectroscopy; Binding mode; Fluorescence image; FREE-RADICAL POLYMERIZATION; II PHOTOINITIATOR; ETHIDIUM-BROMIDE; GROOVE BINDING; LIGHT; COMPLEX; ACID; VISUALIZATION; CYTOTOXICITY; ANTICANCER